Teaching modernization : Spanish and Latin American educational reform in the Cold War - Martín García, Óscar José; Delgado Gómez-Escalonilla, Lorenzo (New York : Berghahn Books, 2019)
"In the 1960s and 1970s, the educational systems in Spain and Latin America underwent comprehensive and ambitious reforms that took place amid a "revolution of expectations" arising from decolonization, global student protests, and the antagonism between capitalist and communist models of development. Deploying new archival research and innovative perspectives, the contributions to this volume examine the influence of transnational forces during the cultural Cold War. They shed new light on the roles played by the United States, non-state actors, international organizations and theories of modernization and human capital in educational reform efforts in the developing Hispanic world"--
Educational reform, modernization, and development : a Cold War transnational process / Óscar J. Martín García and Lorenzo Delgado Gómez-Escalonilla -- US assistance to educational reform in Spain : soft power in exchange for military bases / Lorenzo Delgado Gómez-Escalonilla and Patricia de la Hoz Pascua -- Forerunners of change? : the Ford Foundation's activities in Francoist Spain / Francisco Rodríguez-Jiménez -- Educational transfer and local actors : international intervention in Spain during the late Franco period / Mariano González-Delgado and Tamar Groves -- Much ado about nothing? : lights and shadows of the World Bank's support of Spanish aspirations to educational modernization (1968-1972) / David Corrales Morales -- US foreign policy toward Spanish students : youth diplomacy, modernization, and educational reform / Óscar J. Martín García -- How a Cold War education project backfired : modernization theory, the alliance for progress, and the 1968 education reform in El Salvador / Héctor Lindo-Fuentes -- Passing through a critical moment : the United States and Brazilian university reform in the 1960s / Colin M. Snider -- Between the eagle and the condor : the Ford Foundation and the modernization of the University of Chile (1965-1975) / Fernando Quesada -- Between modernization and university reform (1957-1973) : technical assistance from UNESCO to the University of Concepción / Anabella Abarzúa Cutroni.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Educational change -- Spain -- History -- 20th century; Educational change -- Latin America -- History -- 20th century; Education and state -- Spain -- History -- 20th century; Education and state -- Latin America -- History -- 20th century; Cold War -- Social aspects -- Spain; Cold War -- Social aspects -- Latin America; Enseignement -- Réforme -- Espagne -- Histoire -- 20e siècle.; Enseignement -- Réforme -- Amérique latine -- Histoire -- 20e siècle.; Éducation -- Politique gouvernementale -- Espagne -- Histoire -- 20e siècle.; Éducation -- Politique gouvernementale -- Amérique latine -- Histoire -- 20e siècle.; Guerre froide -- Aspect social -- Espagne; Guerre froide -- Aspect social -- Amérique latine; EDUCATION / Educational Policy & Reform / General; Education and state; Educational change; Social aspects; Latin America; Spain; 1900-1999; History